Relación entre la cuenta corriente de la balanza de pagos y la inversión extranjera directa: un estudio para la economía peruana, periodo 1994 - 2019 - Carrasco Dominguez, Diana Marilyn (2022)
The study investigates the relationship between the current account of the balance of payments (CCBP) and foreign direct investment (FDI) in Peru, using the Granger technique and the vector error correction model (VECM). The results show that the CCBP and FDI are cointegrated and maintain a long-term relationship. FDI has a negative effect on the CCBP. However, the coefficients of the lagged variables indicate that there is no causality in the short term. The speed of adjustment is 23.22%, so the discrepancy between CCBP and FDI is corrected in one quarter. The Granger-way test shows one-sided direction from FDI to CCBP. Therefore, it is observed as a policy implication that FDI can cause deterioration in the external sector, suggesting a review of the benefits of foreign direct investment.